1995
DOI: 10.1039/an9952000845
|View full text |Cite
|
Sign up to set email alerts
|

New concepts of iron and aluminium chelation therapy with oral L1 (deferiprone) and other chelators. A review

Abstract: The introduction of oral chelation therapy with the alpha-ketohydroxypyridine chelator 1,2-dimethyl-3-hydroxypyrid-4-one (L1, INN/BAN: deferiprone) in iron- and aluminium-overloaded patients has been initiated in over 15 countries in the last 7 years. Over 600 patients with various conditions, in 26 centres have received L1, in some cases daily for over 5 years. In the vast majority of iron-loaded patients, doses of 55-100 mg kg-1 of L1 resulted in urinary iron excretion levels greater than those accumulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(43 citation statements)
references
References 30 publications
0
42
0
1
Order By: Relevance
“…Labile iron that is likely to be accessible to DFP is assumed to be bound to several possible ligands (eg, citrate, ATP) and to be in dynamic equilibrium between Fe(II) and Fe(III) as dictated by the redox status of the intracellular environment. 38,39 DFP competes effectively for labile cell iron both in vitro and in vivo, 32 and in individuals with normal iron balance it raises serum iron levels, indicating mobilization of tissue iron. 12 This was also observed with isolated cells (Figures 3,4), where DFP readily chelated iron bound to the EDTA analog CALG in endosomes and nuclei and was indicated in other systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Labile iron that is likely to be accessible to DFP is assumed to be bound to several possible ligands (eg, citrate, ATP) and to be in dynamic equilibrium between Fe(II) and Fe(III) as dictated by the redox status of the intracellular environment. 38,39 DFP competes effectively for labile cell iron both in vitro and in vivo, 32 and in individuals with normal iron balance it raises serum iron levels, indicating mobilization of tissue iron. 12 This was also observed with isolated cells (Figures 3,4), where DFP readily chelated iron bound to the EDTA analog CALG in endosomes and nuclei and was indicated in other systems.…”
Section: Discussionmentioning
confidence: 99%
“…14 Yet, despite DFP's brain accessibility, major effects on CNS function have not been reported. 32,44 Whether DFP can alter the iron balance in the brain by shuttling iron across the BBB remains an open question. The absence of iron loading of the CNS in iron-overload conditions indicates that neither transferrin-bound nor non-transferrin-bound iron is able to freely cross the BBB.…”
mentioning
confidence: 99%
“…Regarding aluminium() and iron(), there is a need for new, safe, inexpensive, efficient, and orally effective chelators, [1][2][3] because the existing ones, i.e. desferrioxamine and deferiprone, have a number of drawbacks, including oral inefficacy and the high cost for the former, [4][5][6] and several toxic side effects and controversial efficiency for the latter. [5][6][7][8] In a previous work [9] we proposed hydroxypyridinecarboxylic acids (HPs) as new possible chelating agents for aluminium() in view of several promising properties such as their lack of toxicity (references in ref.…”
Section: Introductionmentioning
confidence: 99%
“…This conclusion was based on the documented capacity of L1 to mobilize Fe in vivo 23 and from cells in vitro 4 and to transfer it to Fl-DFO in vitro ( Figure 5). Moreover, we found that the increase in serum Fe induced by L1 and identified as DCI (Figure 3), was paralleled by an increase in the total serum Fe content measured by the acid-bathophenanthroline method (data not shown).…”
Section: Mobilization Of Fe By L1 and Its Transfer To Dfo In Vitro Anmentioning
confidence: 99%